2021
DOI: 10.3389/fneur.2021.758481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Dosing of Vibrotactile Coordinated Reset Stimulation in Motor and Non-motor Symptoms of Parkinson's Disease: A Study Protocol

Abstract: Enhanced neuronal synchronization of the subthalamic nucleus (STN) is commonly found in PD patients and corresponds to decreased motor ability. Coordinated reset (CR) was developed to decouple synchronized states causing long lasting desynchronization of neural networks. Vibrotactile CR stimulation (vCR) was developed as non-invasive therapeutic that delivers gentle vibrations to the fingertips. A previous study has shown that vCR can desynchronize abnormal brain rhythms within the sensorimotor cortex of PD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(131 reference statements)
0
0
0
Order By: Relevance
“…Preliminary clinical experience in stroke patients has suggested that such peripheral sensory stimulation can improve recovery and rehabilitation in stroke survivors (9)(10)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Interestingly, similar benefits have been demonstrated in patients with Parkinson's disease, and PSS has also shown promise following traumatic brain injury and in inflammatory, auto-immune conditions such as multiple sclerosis (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 97%
“…Preliminary clinical experience in stroke patients has suggested that such peripheral sensory stimulation can improve recovery and rehabilitation in stroke survivors (9)(10)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Interestingly, similar benefits have been demonstrated in patients with Parkinson's disease, and PSS has also shown promise following traumatic brain injury and in inflammatory, auto-immune conditions such as multiple sclerosis (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 97%